Teaching at college and university effective strategies and key principles - Moore, Sarah (Open UP study skills, 2007)
Presents theory and literature from the fields of organizational behaviour, learning, pedagogy and education. This book examines evidence-based insights in order to help support the delivery of academic expertise both within and beyond classroom settings. It also encourages teachers to adopt a reflective orientation.